# 3n-2n^4+n+7n^4-2n=

## Simple and best practice solution for 3n-2n^4+n+7n^4-2n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3n-2n^4+n+7n^4-2n= equation:

Simplifying
3n + -2n4 + n + 7n4 + -2n = 0

Reorder the terms:
3n + n + -2n + -2n4 + 7n4 = 0

Combine like terms: 3n + n = 4n
4n + -2n + -2n4 + 7n4 = 0

Combine like terms: 4n + -2n = 2n
2n + -2n4 + 7n4 = 0

Combine like terms: -2n4 + 7n4 = 5n4
2n + 5n4 = 0

Solving
2n + 5n4 = 0

Solving for variable 'n'.

Factor out the Greatest Common Factor (GCF), 'n'.
n(2 + 5n3) = 0

Subproblem 1Set the factor 'n' equal to zero and attempt to solve:

Simplifying
n = 0

Solving
n = 0

Move all terms containing n to the left, all other terms to the right.

Simplifying
n = 0
Subproblem 2Set the factor '(2 + 5n3)' equal to zero and attempt to solve:

Simplifying
2 + 5n3 = 0

Solving
2 + 5n3 = 0

Move all terms containing n to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 5n3 = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 5n3 = 0 + -2
5n3 = 0 + -2

Combine like terms: 0 + -2 = -2
5n3 = -2

Divide each side by '5'.
n3 = -0.4

Simplifying
n3 = -0.4

The solution to this equation could not be determined.

This subproblem is being ignored because a solution could not be determined.Solutionn = {0}`